Palladium-Catalyzed Chemoselective Catellani ortho-Arylation Reactions and Their Applications in Natural Products Synthesis - Sui, Xianwei; Zhu, Rui; Gu, Zhenhua (Synlett, 2013)
This review gave a brief account for the palladium-catalyzed chemoselective Catellani ortho-arylation reactions. Two possible methods were discussed which were usually used to control the chemoselectivities of these ortho-arylation reactions. Additionally, examples of the Catellani reaction in natural product synthesis are also reviewed.
Keywords: arylation; palladium; Heck reaction; multicomponent reaction; alkaloids